A Socio-Pragmatic Analysis of Responses to Impoliteness in some Selected English and Arabic Literary Texts - Al-Muslehi, Mahmood A.; Al-Utbi, Mahdi I. (Al-Adab Journal, 2021)
A great number of studies have dealt with impoliteness within the area of pragmatics, but it seems the responses to impoliteness as a socio-pragmatic phenomenon have been somehow neglected. Therefore, by employing a model of impoliteness strategies proposed by Culpeper (2005), this paper aims at investigating of the responses to impoliteness from socio-pragmatic view in English and Arabic literary texts to examine the types of responses to impoliteness, and the ways in which the characters make use of their social power to perform impolite behaviors or utterances to respond to others so as to achieve certain social goals. It worth mentioning that this paper has tackled the responses qualitatively and quantitatively because it explains a specific socio-pragmatic phenomenon which is Impoliteness. The results of the study show that the responses to impoliteness are various in English and Arabic plays which hearers make use of context or their social power to respond to attackers.